Novel methodology for the calculation of transformers in power multilevel converters (2015)
(Eng) This paper presents a new methodology for the correct design of transformers used in power multilevel inverters common source type. The proposed methodology represents a solution to the problems of distortion in the waveform, voltage drop and loss of efficiency caused by the miscalculation of the transformer using conventional methodology. To validate the methodology two prototypes under different perspectives were built, conventional and proposed, in order to verify the results, which support the solution to the problems described and shown an improvement in performance of the power converter.